Supplemental family leave provision and employee performance: Disentangling availability and use. Issue 3 (4th February 2022) - Begall, Katia; van Breeschoten, Leonie; van der Lippe, Tanja; Poortman, Anne-Rigt
Abstract: The purpose of this study is to investigate whether the provision of supplemental family leave elicits higher work effort and extra-role behavior in employees. Drawing on arguments derived from signaling theory we test whether the beneficial effects of providing longer or better paid family leave on performance exist for all employees, or whether they are limited to the group who either took advantage of the supplemental leave in the past or is likely to do so in the future. In addition, the mechanism proposed by organizational support theory by which supplemental leave is expected to affect employee performance - by increasing affective organizational commitment - is tested. The hypotheses developed are tested using European multilevel organization-data (Van der Lippe et al., 2016a ) on 11, 011 employees in 869 departments or teams, and 259 organizations. The results indicate that perceived availability of supplemental family leave relates positively to employees' contextual performance, partially by increasing organizational commitment. This effect is found irrespective of actual use of family leave and is not moderated by characteristics relating to future use such as having young children, being of childbearing age or being female.